Nursing Management of Orthostatic Hypotension in Older People with Parkinson’s Disease - Yaemmisri, Waraphorn; Mongkhonittivech, Nongyao (Journal of The Royal Thai Army Nurses, 2021)
Orthostatic or postural hypotension is a common symptom among older people, particularly with Parkinson’s disease. The etiologies include autonomic failure from advancing age, receiving some medications and decrease blood circulation. Consequently, nurses should have knowledge, understanding about intervention and advice older people and/or their relatives about orthostatic hypotension to observe, take care older people when occurring orthostatic hypotension. In addition, this can prevent reoccurrence that will ensure elderly with Parkinson’s disease safety, reduce complications and improve their quality of life.